Pengaruh Intensitas Modal, Return On Asset, Dan Debt To Asset Ratio Terhadap Agresivitas Pajak Pada Perusahaan Sektor Pertanian Yang Terdaftar Dibursa Efek Indonesia Periode 2021-2023 - Munawaroh, Munawaroh; Miswaty, Miswaty; Karlinda Sari, Dika (Jurnal GeoEkonomi, 2025)
This research aims to test the influence of Capital Intensity, Return On Assets and Debt to Asset Ratio. The data used in this research are financial reports of agricultural sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The type of research used is quantitative research. The sampling technique used a purposive sampling method which resulted in 74 company samples with a total population data obtained of 103 from 3 periods. The data analysis method used is descriptive statistical analysis and multiple linear regression analysis. The test equipment used is the classical assumption test, coefficient of determination test and t test. The results of this research state that Capital Intensity has a significant effect on Tax Aggressiveness. Meanwhile, Return On Assets and Debt To Asset Ratio do not have a significant effect on Tax Aggressiveness.